Visuospatial working memory and attention control make the difference between experts, regulars and non-players of the videogame League of Legends - Valls-Serrano, Carlos; De Francisco, Cristina; Vélez-Coto, María; Caracuel, Alfonso (Frontiers in Human Neuroscience, 2022)
Video games have been postulated as an emerging field for studying the cognition-expertise relationship. Despite this, some methodological practices hinder scientific advance (e.g., heterogeneous samples, an ambiguous definition of expertise, etc.). League of Legends (LOL) is a massively played video game with a moderately defined structure that meets the requirements to overcome current study limitations. The aim of this study was to analyze cognitive differences among expert LOL players, regular LOL players, and non-videogame players. A sample of 80 participants was enrolled in three different groups of expertise. Participants were evaluated with behavioral tests of working memory, attention, cognitive flexibility, and inhibition. Kruskal-Wallis tests for group comparison showed that the experts performed significantly better than regular players and non-videogame players in the working memory test. Significant differences were also found between players and non-videogame players in the attention test. Methodological implications for future research in neuroscience and human-computer interaction are discussed.